اردو رسم الخط اور املا کے فنی و لسانی مباحث: TECHNICAL AND LINGUISTIC DISCUSSIONS OF URDU SCRIPT AND SPELLING (Contemporary Journal of Social Science Review, 2025)
The evolution of Urdu orthography (Imla) and its script (Rasm-ul-Khat) represents a dynamic intersection of historical tradition, phonetic necessity, and modern technological adaptation. This article provides a comprehensive analysis of the technical and linguistic discourses surrounding the Urdu writing system. Tracing its origins from Aramaic and Nabataean roots through the refinement of Naskh and * تعلیق (Taliq)* to the aesthetic brilliance of Nastaliq, the research explores how Urdu integrated Indo-Aryan sounds—such as retroflexes and aspirates—into a Perso-Arabic framework. The study delves into critical linguistic debates, including the number of alphabets, the dual status of Hamza as a letter or a diacritic, and the orthographic treatment of Alif Maqsura. Furthermore, it examines the transition from classical orthographic inconsistencies found in early manuscripts and the letters of Mirza Ghalib to the modern standardization efforts led by institutions like the National Language Promotion Department (Muqtadra) and Urdu Academy Delhi. A significant portion of the article is dedicated to the digital age, analyzing how standardized keyboards and Unicode Nuri Nastaliq fonts have addressed the challenges of modern computing and social media. The research concludes that while phonetic simplification is a recurring scientific demand, the current Urdu orthography serves as a vital guardian of the language's etymological identity and cultural heritage in the era of Artificial Intelligence.